SPEECH ACTS AND THE COMMON PROBLEMS INVOLVED IN A HUMOR TEXT - Deasy Ari Astuti; Oktiva Herry Chandra (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2021)
People need humor for enjoying entertainment and amusement. Its function is getting wider not only to make people laugh but also to make social activity. This aricle aims to figure out kinds of speech act people generally used to show their intention in humor. The data were collected from Reader’s Digest magazine using no-participatory. The data are utterances that become the punch line of humor as units to analyze. The result shows that there are two speech acts of humor texts, that is, representative and commissive. They are uttered in form of indirect speech in which the function and the mood of utterances are not in line. The punch lines of humor are triggered by some topics, namely the characters or bad traits of someone, marriage issues which cover the anxiety of getting old, passing by the time of living together as husband and wife, job and position at workplace, public services which include mistake, satisfaction, dissatisfaction, and complaint people met when having the service in public places, and other problems related to various aspects of life.Keywords: humor text, indirect speech, representative, commissive, puch lines of humor